TREND EKSPOR INDONESIA KE 3 NEGARA ASEAN SINGAPURA, FILIPINA DAN LAOS (SFL) - Dewi Mahrani Rangkuty; Bakhtiar Efendi; Noni Ardian (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
Indonesia as one of among emerging markets enhances the economy through international export trade activities. By using the 2005-2018 time-series data period, the aim of the research was to analyze Indonesia's export performance trend to 3 ASEAN countries Singapore, Philippines and Laos. The results showed that the trend of Indonesia's exports to 3 countries of the ASEAN region for the next 10 years showed a positive and bearish bullish trend in the year 2019-2028. In addition, there is a long-term balance relationship between the research variables. The rate and export of Indonesia to Singapore have a causality relationship. And there is no causal relationship between the research variables in the Philippine and Laos countries. The Ministry of Trade is recommended for the improvement of Indonesia's export performance focusing on semi-finished and finished products. Because of the achievement of trade balance surplus for encouraging an accelerated increase in Indonesia's economic growth.